Subway Expansion and Traffic Flow: A Spatiotemporal Analysis of Urban Congestion Dynamics - Mincong Tang; Borut Buchmeister; Daqing Gong; Gang Xue; Bui Thanh Khoa (Tehnički Vjesnik, 2025)
This study investigates the impact of new subway line openings on urban road traffic congestion through a spatiotemporal analysis. Focusing on the southern section of Beijing Subway Line 8, which commenced operation in late 2018, the research employs a difference-in-differences (DID) approach to analyze traffic congestion data from 2018 to 2021. The study examines both short- and long-term effects on road congestion in areas surrounding the new subway stations. The findings reveal that the effects of subway expansions on congestion vary by time of day and diminish over time. While the subway extension was intended to alleviate congestion, its impact is limited during morning peak hours but more pronounced during evening peaks. These results highlight the complexity of urban traffic management and underscore the importance of considering the interplay between subway expansions and existing traffic systems to optimize congestion mitigation strategies.